Investigation of Thermal Comfort at Different Temperature Settings for Cooling in University Building / Mohd Sabri Mustapa ...[et al.] - Mustapa, Mohd Sabri; Shaikh Salim, Sheikh Ahmad Zaki; Mat Ali, Mohamed Sukri; Rijal, Hom Bahadur (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This paper presented the results of a study conducted on thermal comfort in a postgraduate office of the Malaysia Japan International Institute of Technology (MJIIT, UTM, Kuala Lumpur). The aim of the study was to verify the thermal comfort associated with different air conditioning (AC) thermostat set point temperatures in the cooling (CL) mode. The relevant temperature set points were 20 °C, 24 °C, and 28 °C, as well as the Japanese so-called 'cool biz mode' set point of 28 °C. The thermal sensation vote (TSV) in relation to these CL modes were -0.4, 0.0, 0.8, and -0.1, respectively. These results indicated that at the CL mode of 28 °C, the occupants felt slightly warmer compared to the CL modes of 20 °C, 24 °C, and the cool biz mode. The results of the linear regression analysis indicated the thermal comfort range as 25.3 °C to 26.2 °C, which was close to the range of 25.6 °C to 26.1 °C indicated by employing Griffiths' method.